Chronic idiopathic axonal polyneuropathy: Prevalence of pain and impact on quality of life. Issue 1 (25th November 2018) - Zis, Panagiotis; Sarrigiannis, Ptolemaios G.; Rao, Dasappaiah G.; Hewamadduma, Channa; Hadjivassiliou, Marios
Abstract: Background and Aim: Chronic idiopathic axonal polyneuropathy (CIAP) is a term describing axonal neuropathies of insidious onset, with slow or no progression of the disease over at least 6 months and with no etiology being identified despite appropriate investigations. We aimed to establish the prevalence of pain in patients with CIAP and investigate the impact of pain on quality of life (QoL). Methods: All consecutive patients with CIAP attending a specialist neuropathy clinic were invited to participate. Pain was assessed via the DN4 questionnaire and the visual analogue scale (VAS). Overall Neuropathy Limitations Scale (ONLS) was used to assess the severity of neuropathy. The SF‐36 questionnaire was used to measure participants' quality of life. Results: Fifty‐five patients with CIAP were recruited (63.6% male, mean age 73.4 ± 8.7 years). Based on the DN4 questionnaire, peripheral neuropathic pain was present in 33 patients (60.0%). After having adjusted for age, gender and disease severity pain showed significant negative correlations with the energy/fatigue domain of QoL ( β = −0.259, p = 0.049), with the emotional well‐being domain ( β = −0.368, p = 0.007) and the general health perception domain ( β = −0.356, p = 0.007). Conclusion: Pain is very prevalent in CIAP and is associated with poorer emotional well‐being, worse general health perception, and increased fatigue. Abstract : Pain is very prevalent in chronic idiopathic axonal polyneuropathy and has a significant impact especially to the energy/fatigue and emotional well being of the patients.